Signs of proof of financial insolvency are in context of crime of taking to bankruptcy - Улибіна, Вікторія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The key term of crime of taking to bankruptcy of item is examined in the article. 219 KK of Ukraine, inparticular «proof financial insolvency». Selected eсonomik and legal features of proof financial insolvency.